THE ROLE OF SPIRITUAL AND MORAL EDUCATION IN ELIMINATING NEGATIVE MANIFESTATIONS IN ADOLESCENT BEHAVIOR - Sattorov Fozil Fakhritdinovich (European Journal of Humanities and Educational Advancements, 2023)
The article analyzes one of the urgent problems of modern educational practice - prevention of deviant behavior of adolescents as a necessary condition for the progressive and safe development of society in particular and civilization in general.